THE ROLE OF LOCAL WISDOM OF THE BAJO MUARA TRIBE IN MANAGING THE CLEAN AND HEALTHY LIVING BEHAVIOR PROGRAM - Asri, Abdul Malik Darmin; Indang, Wa Ode; Waru, Hamsia L.; Hikma, Wa Ode Erty; Akbar, Hairil (International Journal of Health Science & Medical Research, 2025)
Clean and Healthy Living Behavior (PHBS) is a conscious effort enabling families to be independent in health, actively engage in health activities, and contribute to community health. Purpose of the research is explores the role of local wisdom in shaping the Bajo Muara tribe's understanding and adoption of PHBS. The type of research used is qualitative research employs an ethnographic approach in Benteng Village, Lasalimu District, Buton Regency, from June to August 2024. Thirteen participants were selected using purposive sampling. Data were gathered through observation, interviews, documentation, and Focus Group Discussions (FGD). Results: The Bajo Muara community faces challenges in adopting PHBS due to social norms. Health access is limited, and childbirth often relies on traditional healers or midwives, with some births occurring at home. Initial breast milk (colostrum) is discarded as unsuitable, while formula and sachet milk are widely used. Diets lack balanced nutrition. Though the government provides clean water, distribution issues force residents to fetch water from the mainland. Open defecation in the sea remains prevalent. Smoking, common among both men and women, averages 1–2 packs daily. Washing habits are practiced to maintain cleanliness. The implementation of PHBS among the Bajo Muara community is hindered by deeply rooted social norms, limited health access, and challenges in infrastructure and education.